AN ANALYSIS OF ILLOCUTIONARY SPEECH ACTS IN INSTAGRAM POSTS AND COMMENTS BY THIRD-SEMESTER ENGLISH EDUCATION STUDENTS - Sigalingging, Grace Joy; Tampubolon, Sahlan; Siahaan, Sahat Taruli (Dharmas Education Journal (DE_Journal), 2020)
This Research Aimed To See The Analysis Of Illocutial Speech Act On Instagram Posts And Comments Of Third Semester English Education Students At Hkbp Nommensen. After analyzing the illocutionary acts in the Instagram posts and comments of third-semester English Education students at Nommensen HKBP University, the following conclusions can be drawn: The illocutionary speech acts found in the data include assertives, directives, and expressives. The data was collected from the Instagram accounts of third-semester English Education students, that is, @Icaafrianisitorus, @givalentine_, @novia.as.564, and @cristina_nelvana. Each account focused on different topics. For example, one account focused on emotional expression and social identity, while another emphasized self-confidence and self-validation. Students use assertive acts to express their thoughts, present factual information, and share personal perspectives. Directive acts are employed to influence others' behavior, such as offering advice, making invitations, and encouraging participation in activities. Expressive acts reflect the speaker's emotional state and are used to convey feelings such as gratitude, encouragement, congratulations, and welcome. No commissive or declarative speech acts were found in the data.The most dominant type of illocutionary act found in the data is expressive. This type of speech act is used the most frequently, indicating that students primarily use Instagram for emotional expression, maintaining social connections, and strengthening interpersonal relationships. The prevalence of expressive acts emphasizes the affective nature of their digital communication, focusing on emotional support, social bonding, and self-expression. The absence of commissive and declarative speech acts is likely due to Instagram’s informal and personal nature as a platform, which does not require formal commitments or declarations.In conclusion, this study demonstrates that social media serves as more than just an information-sharing tool; it is a dynamic space for self- expression, emotional connection, and identity formation. The students’ linguistic choices reflect their inclination toward fostering interpersonal relationships, strengthening social bonds, and engaging in meaningful interactions rather than simply exchanging factual content. This highlights the evolving nature of digital communication, where social media platforms facilitate both personal expression and community engagement.